2013
DOI: 10.1111/bcpt.12076
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Attenuates Diet‐Induced Hepatic Steatosis by Activating AMP‐Activated Protein Kinase

Abstract: Curcumin is a well-known component of traditional turmeric (Curcuma longa), which has been reported to prevent obesity and diabetes. However, the effect of curcumin on hepatic lipid metabolism remains unclear. The aim of this study was to examine the effects of curcumin on hepatic steatosis in high-fat/cholesterol diet (HFD)-induced obese mice. Male C57BL/6J mice were fed a normal diet (ND), HFD or HFD with 0.15% curcumin (HFD+C) for 11 weeks. We found that curcumin significantly lowered the body-weight and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 33 publications
8
69
0
1
Order By: Relevance
“…Metabolic stresses that increase the rate of ATP consumption, such as muscle contraction, or inhibit the catabolic production of ATP, such as oxygen or glucose deprivation, have been well characterized as potent AMPK activators [40][41][42]. AMPK activating activity has also been demonstrated by antidiabetic drugs such as metformin, the adenosine monophosphate (AMP) analog 5-aminoimidazole-4-carboxamide-1-beta-4-ribofuranoside (AICAR), and by several plant-based compounds, including resveratrol, berberine, curcumin, and epigallocatechin-3-gallate [43][44][45][46][47][48].…”
Section: The Hypothesismentioning
confidence: 99%
“…Metabolic stresses that increase the rate of ATP consumption, such as muscle contraction, or inhibit the catabolic production of ATP, such as oxygen or glucose deprivation, have been well characterized as potent AMPK activators [40][41][42]. AMPK activating activity has also been demonstrated by antidiabetic drugs such as metformin, the adenosine monophosphate (AMP) analog 5-aminoimidazole-4-carboxamide-1-beta-4-ribofuranoside (AICAR), and by several plant-based compounds, including resveratrol, berberine, curcumin, and epigallocatechin-3-gallate [43][44][45][46][47][48].…”
Section: The Hypothesismentioning
confidence: 99%
“…A study reported that curcumin improves hypertriglyceridemia and insulin sensitivity through the suppression of protein tyrosine phosphatase 1B (Li et al 2010). Studies in animal models have proved that curcumin effectively prevented high-fat diet induced obesity (Um et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Of the herbal medicines widely used in Korea, Curcuma longa, Alnus japonica, and Massa Medicata Fermentata have also been reported to regulate hyperlipidemia, obesity, insulin resistance, and hepatic steatosis in high fat diet-fed mice, obese type 2 diabetic mice, and malonyl-CoA decarboxylase-deficient mice (Paik et al, 2012;Zhao et al, 2012;Um et al, 2013). These effects resemble the documented effects of PPARα activation on lipid metabolism and obesity regulation.…”
Section: Discussionmentioning
confidence: 86%
“…Massa Medicata Fermentata is frequently used in combination with other herbs to exert pharmacological effects (Li, 2006). Moreover, individual three ingredients of GGH(4) regulate lipid metabolism and reduce hyperlipidemia, obesity, insulin resistance and hepatic steatosis (Paik et al, 2012;Zhao et al, 2012;Um et al, 2013). These reports led us to hypothesize that GGH(4) would efficiently regulate adipocyte lipid accumulation and obesity.…”
Section: Introductionmentioning
confidence: 99%